Social mobility and inequality between groups - Patricia Funjika; Rachel M. Gisselquist (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The relationship between social mobility and inequality is well studied in the literature, but far greater attention has been paid to 'vertical' than to 'horizontal' inequality. This paper focuses on mobility and horizontal inequality between ethnic, racial, and culturally-defined groups. Not only is persistence in horizontal inequality due to low intergenerational mobility overall, it argues, it also is explained by the lower mobility of disadvantaged compared with advantaged groups in many societies. Group-based discrimination, among other factors, contributes. The paper further explores empirical data on this relationship across countries and shows how it may be especially problematic in the countries of the Global South.
Keywords: D63; J62; J15; J71; 330; social mobility; horizontal inequality; ethnic inequality; intergenerational mobility; discrimination